Pengembangan Antarmuka Website PPPA Daarul Qur'an Malang Dengan Menggunakan Metode Goal Directed Design - Alif Akbar Tejamukti; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PPPA Daarul Qur'an (DAQU) is a charitable institution that professionally and accountably organizes an establishment for people based on tahfizhul Qur'an. DAQU Malang, as branch office wants improvements to their website in aspects of appearance, information structure, and addition of charity reports features to gain better credibility. This research objective is to generate design of DAQU Malang website by using Goal-Directed Design method. Goal-Directed Design method has six phases that providing solution for designing website that suit with user's goal. Starting with research phase for collecting needs and conditions desired by stakeholders and users formed into statement of work. Followed by modeling phase, producing persona that describe group of stakeholder and user within 6 variables. Next, requirement definition phase, mapping needs of the website and its environment in descriptive table form and 25 web domains. Then, design framework phase, generating design of information structure into hierarchical task analysis based on card sorting and producing wireframe as the website interface design. Next, design refinement phase, refining of interface design as prototype hi-fi. Lastly, design support phase, practicing a qualitative test evaluation with user testing method that generate positive and negative feedback. This design support phase, quantitative testing has also be done by using the SUPR-Q questionnaire and generate usability, credibility, appearance and loyalty value within 74,57% of all aspect. These value is categorized as C value which means that overall developed website had been good value and acceptable by the respondents.